The trouble with mirrors : an Alix London mystery - Elkins, Charlotte; Elkins, Aaron J. (Elkins, Charlotte. Alix London mystery., 2016)
Alix London, the art restorer and FBI consultant renowned as the Art Whisperer, can spot a counterfeit masterpiece before the paint even dries. What she can't see is why an elite European art dealer would offer her big money for a little mirror that's no more than a homemade gift from her beloved uncle Tiny. Not that Alix would part with it at any price. But when the mirror is abruptly stolen from her home, she realizes that someone sees more in the looking glass than mere sentimental value. When her uncle Tiny disappears mysteriously just after the mirror is stolen, the simple art theft becomes a personal and professional challenge Alix can't ignore. With backup from her friends in the FBI, her game-for-anything pal Chris, and an aging-but-dogged Italian police detective, she delves into the puzzling case, only to find that there is much more to this theft than meets the eye. Once the Mafia shows up on the scene, Alix's mission becomes a do-or-die race to find the one possible man with all the answers.